Evaluating mobile conditional cash transfers for improving immunization coverage in Pakistan. (30th September 2020) - Chandir, S; Siddiqi, D A; Khan, A A; Abdullah, S; Dharma, V K; Shah, M T; Khan, A J
Abstract: Background: Despite progress in increasing immunization coverage, poor uptake of vaccines remains a challenge, particularly in LMICs. In part, this is due to the poor socio-economic status of caregivers, lack of motivation, and parental procrastination. While there is evidence that large (≥100 USD) incentives can overcome these problems, research on small incentives that are more appropriate for an LMIC setting is sparse. Our study addresses this gap by evaluating the impact of small (≤12 USD) CCTs in increasing immunization coverage for children under the age of two. Methods: A 2-year program utilizing two small incentive schemes of different amounts (high: USD9; low: USD5) was implemented in Shikarpur District, Pakistan. Caregivers (with children 0-24 months) visiting any of the 33 study immunization centers were given the opportunity to enroll. All consenting parent-child pairs were randomized in one of the two incentive schemes and incentives were disbursed following each immunization visit, using mobile money. A baseline and end-line survey was conducted to evaluate changes in pre-post coverage. Results: A total of 63, 336 participants were enrolled between March 2016 - April 2018, of which 41, 483 were randomized in the high or low incentive schemes (remaining caregivers were enrolled in the no-incentive group). Results show a 13% and 28% increase in age-appropriate coverage for Measles-1 (M1) and fully immunized children (FIC) compared to the baseline (FIC:16%, M1: 38%). There was no difference in M1 coverage between the high and low incentive schemes. Discussion: Small CCTs have induced positive behavioral change and are a powerful tool for improving immunization coverage and compliance within LMICs. Key messages: Small mobile conditional cash transfers (USD<12) can serve as nudges to parents and lead to behavioral shifts resulting in improved immunization outcomes for children. There was no significant difference in outcomes between high and low incentives, indicating that small mobile conditional cash transfers were equally effective in improving immunization coverage.